Pharmacovigilance reporting during seasonal malaria chemoprevention campaign: Findings from northern Nigeria - Kunle Rotimi; Jimmy Aiden; Chrysanthus Dabes; Kenneth Maduka; Daniel Oguche; Ademola Joshua Itiola; Olusola Oresanya (Scientific African, 2022)
Background: Seasonal malaria chemoprevention (SMC) campaign is known to reduce malaria-related morbidity and mortality among children aged 3 -59 months in the Sahel regions of Africa. However, the success of the intervention may be adversely affected by the absence of a robust pharmacovigilance system to monitor safety. This paper aims to describe our pharmacovigilance reporting experience during the campaigns conducted across seven states in Nigeria in 2020. Methods: The SMC campaigns were held over four cycles from July to November 2020, with nearly 12 million eligible children reached by trained community drug distributors. Suspected adverse drug reactions were reported routinely through the national pharmacovigilance (PV) system. Completed PV forms submitted to the National Agency for Food, Drugs Administration and Control were retrieved and analyzed. Results: The adverse drug reaction (ADR) reporting across the seven states was low, with no ADR reports from five states. The ADRs reported included abdominal pain, weakness, diarrhea, fever, rash, and vomiting. Vomiting was the most reported ADR, accounting for almost half (28/57) of all reported cases. Children aged 12–59 months accounted for most (∼86%, 49/57) of the ADR reports, with over 70% (40/57) of these reports completed by community health extension workers. The system organ classification of ADRs showed that the gastrointestinal system was mainly affected (65%, 37/57). Conclusion: Our experience suggests gaps with the pharmacovigilance surveillance system, highlighting the need to consider an active surveillance system, address behavioural factors, and explore the use of a digital reporting system.